“Gegar Budaya” Pekerja di Perusahaan Korea: Studi Kasus Pada Alumni D III Bahasa Korea Sekolah Vokasi UGM - Supri - Adianto (Jurnal Gama Societa, 2018)
Culture shock phenomenon is one of society life element that is very interesting to be examined. Culture shock is a common problem to newcomer in new place. Culture shock rise from several factors, such as communication factors, technological factors, geographical factors, daily used language factors, economics factors, custom factors and religious factors. Objective of study are to examine how to minimize culture shock by understanding several social problem related to culture shock and the solution related to culture shock.The research objects are D3 Bahasa Korea (Korean Language Department) alumni, especially batch 2013 who works in Korean company in Indonesia. Quantitative research applied based on questionnaire and in depth interview.  The results of this study are the type of culture shock experienced by alumni and the solution of the culture shock. There are several solution could be applied by alumni who are targeting to work in Korean company and alumni who work in Korean company.